Experimental Investigation on the Engine Performance and Exhaust Emissions of Emulsified Palm Biodiesel Blends on a Diesel Engine - W. N., Maawa; R., Mamat; I. M., Yusri; Yasar, M. (IOP Publishing, 2019)
World energy demand, which is amplified multi-fold day-by-day due to the transportation, urbanization, industrial revolution and electricity generation give severe environmental consequences. The effective solution to steer clear of this problem is by using biodiesel-water emulsification. In the present study, pure diesel, diesel-biodiesel blend (B20) and emulsified diesel-biodiesel blend with different percentage of water 5% (B20E5), 10% (B20E10), 20% (B20E20) and 30% (B20E30) were prepared to be operated in a diesel engine to study engine performance in terms of brake specific fuel consumption (BSFC) and brake thermal efficiency (BTE), and emissions in terms of nitrogen oxides (NOx), carbon dioxides (CO2) and hydrocarbons (HC). Emulsifiers Sorbitan Monoleate (Span 80) and Polyoxyethylene Sorbitan Monoleate (Tween 80) were used to prepare emulsion fuels. The engine was run at constant engine speed 2500 rpm and three different loads, 20%, 40% and 60%. The results showed that highest BSFC reduction of 6.68% achieved by B20E5. The B20E30 give highest improvement in term of BTE which is 32.56% compared to diesel. A total of 17.29% reduction of NOx gained by B20E30 compared to conventional diesel. Therefore, the emulsification of biodiesel blend is suitable as an alternative technique to improve engine performance and emissions.